Respuesta :
Answer:
7 ft 10 inches
Step-by-step explanation:
12 ft 3 inches
- 4 ft 5 inches
--------------------------
We need to borrow from the feet to get enough inches
12 inches = 1 ft
Borrow 1 ft from the 12 ft and make it 12 inches
11 ft 12+3 inches
- 4 ft 5 inches
--------------------------
11 ft 15 inches
- 4 ft 5 inches
--------------------------
7 ft 10 inches
Answer:
7 feet 10 inches.
Step-by-step explanation:
4 feet 5 inches = 4*12 + 5 = 48 + 5 = 53 inches.
12 feet 3 inches = 12*12 + 3 = 144 + 3 = 147 inches.
So 12 feet 3 ins - 4 feet 5 inches = 147 - 53 = 94 inches.
94 inches = 94 / 12 = 7 feet 10 inches (answer).